Falsified antimicrobial medicine: A neglected global health crisis contributing to drug resistance - Slade, Erin (Global Health: Annual Review, 2019)
Falsified antimicrobial drugs pose a significant challenge for global public health. Falsified drugs are those that have been intentionally compromised in terms of quality – they may contain too little, wrong or no active ingredient, or may be mislabeled and contain other toxic substances. An estimated 10-30% of medicine globally is falsified, where Sub-Saharan Africa and Southeast Asia are flooded with poor quality antimalarial, antituberculosis and antiretroviral medications. Falsified treatment for these diseases has dangerous implications for health in countries struggling amidst high burdens of infectious disease, under-funded health systems and political instability. This opinion editorial will examine the consequences of falsified antimicrobial medication for malaria, TB and HIV, and will argue that tackling false medicines is a missing piece of the puzzle towards eradicating drug resistance.